Equity valuation of Ryanair Holdings plc - Cruz, Melissa Domingos Pinto da (2023)
This thesis presents an equity valuation analysis of Ryanair Holding plc, one of the leading players in the European airline industry. The focus of this project is to evaluate the worth of the organization and provide an investment recommendation. Two main valuation methodologies were employed to achieve this goal: Discounted Cash Flow (DCF), with a particular focus on FCFF, and Relative Valuation. This analysis considers both quantitative and qualitative factors, such as the enterprise’s financial state, competitive position, and industry outlook. After conducting our comprehensive analysis, we determined that Ryanair holds a target price of 18.30€. In light of the market’s closing price of 14.88€ on March 31, 2023, our findings prove that Ryanair’s shares are currently undervalued. Therefore, we recommend holding or buying the shares, as they present a potential investment opportunity.